Effect of Wheat and Barley Cover Crops on Weed Control, Growth and Yield of Rapeseed under Different Nitrogen Levels - M. Edalat; S. Shahrasbi; S. A. Kazemeini; Y. Emam (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2017)
Cultivation of winter cover crops such as wheat and barley is one of the practical approaches for weeds control in cereal-based rotations. In order to investigate the effect of cover crop species and nitrogen rates on weed control of rapeseed (Brassica napus L.), a field experiment was arranged in split-plot based on a RCBD with three replications during 2013-2014 growing season at Research Field of School of Agriculture, Shiraz University, Shiraz, Iran. Treatments included nitrogen levels (75 and 150 kg N ha-1) as the main factor and cover crops (no cover crop as control, 25% wheat, 50% wheat, 75% wheat, 25% barley, 50% barley and 75% barley) as sub factor. The results showed that there was significant difference between the presence and absence of cover crop and its interaction with nitrogen level in terms of an array of measured traits. The lowest density, dry weight and height of weeds were obtained from the using barley as a cover crop at the presence of both nitrogen rates, suggesting that barley cover crop is more potent to suppress the weeds compared to wheat cover crop. The highest grain yield (5290 kg ha-1) and oil yield (1760 kg ha-1) of rapeseed were obtained from 50% barley cover crop and the highest rapeseed protein percentage (43%) was obtained from using 25% wheat cover crop at 150 kg N ha-1. Overall, the highest grain and oil yields were achieved from application of 150 kg N ha-1 along with using 50% barley cover crop treatment, though the latter combination did not significantly differ from 75 kg N ha-1 at 50% wheat cover crop